Analisis Multisektor Terhadap Klasifikasi Rokok Sebagai Kelompok Makanan : Multisector Analysis on Classifying Cigarettes as Food Category - Utama, Nugraha Maulana; Hidayat, Syarif Imam; Harya, Gyska Indah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
The classification of cigarettes as a food item by Indonesia’s Central Bureau of Statistics (BPS) in household expenditure data has sparked controversy, as it contradicts the definition of food according to several other government institutions. This study aims to analyze inter-agency differences in perspective regarding this classification and assess its implications within the context of public policy. A qualitative descriptive method was used, involving document analysis and in-depth interviews with representatives from BPS, the Food Security and Agriculture Office, the Health Office, the Industry and Trade Office, and the Ministry of Religious Affairs. The findings reveal that BPS relies on the Classification of Individual Consumption According to Purpose (COICOP-18), an international standard issued by the United Nations Statistics Division (UNSD), which categorizes cigarettes under "food and non-alcoholic beverages" for global statistical comparison. However, related agencies firmly oppose this classification, arguing that it conflicts with principles of nutrition, public health, and ethics, and may create public confusion. The divergence of views highlights a lack of policy coordination across sectors and underscores the need for classification systems that better reflect Indonesia’s cultural and social context. This study recommends a reassessment of the use of international standards and stronger inter-agency alignment to ensure classifications serve national health and welfare objectives.